2021
DOI: 10.2337/db20-0883
|View full text |Cite
|
Sign up to set email alerts
|

The SNAG Domain of Insm1 Regulates Pancreatic Endocrine Cell Differentiation and Represses β- to δ-Cell Transdifferentiation

Abstract: The allocation and specification of pancreatic endocrine lineages are tightly regulated by transcription factors. Disturbances in differentiation of these lineages contribute to the development of various metabolic diseases, including diabetes. The insulinoma-associated protein 1 (Insm1), which encodes a protein containing one SNAG domain and five zinc fingers, plays essential roles in pancreatic endocrine cell differentiation and in mature β-cell function. In the current study, we compared the differentiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…5f ). In the trunk endocrine transition, YBX1 upregulated INSM1 , which is a key regulator in the endocrine lineage and has been reported to participate in mouse islet development and β-cell identity maintenance 52 , 53 . INSM1 , in turn, upregulated a series of genes confined to endocrine lineages, including FEV and PAX6 , which are reported to be key regulators in the development of EP cells and to trigger a complex network that sustains EP identity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5f ). In the trunk endocrine transition, YBX1 upregulated INSM1 , which is a key regulator in the endocrine lineage and has been reported to participate in mouse islet development and β-cell identity maintenance 52 , 53 . INSM1 , in turn, upregulated a series of genes confined to endocrine lineages, including FEV and PAX6 , which are reported to be key regulators in the development of EP cells and to trigger a complex network that sustains EP identity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The function of HDAC in EP cell differentiation in the human pancreas still needs to be validated. Moreover, in a combined analysis with scATAC-seq data, we identified TFs in trunk cells governing cell fate choice in endocrinogenesis; these TFs included YBX1 , which upregulated INSM1 , a reported important regulator in mouse islet development 52 , 53 , to favor endocrine lineage differentiation. Our data suggested that ID4 , which upregulated HES4 in trunk cells, could suppress endocrine differentiation and favor ductal lineage development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased somatostatin in Hhex KO pancreatic islets caused impaired paracrine inhibition of insulin released from beta cells (137). In beta cells the Hhex locus is targeted by Lsd1 which facilitates H3K3me1/2 methylationmediated repression of Hhex preventing beta to delta cell transition (Figure 3) (138). This suggested that compromised paracrine control may be partly responsible for T2D through the acceleration of beta cell exhaustion and failure (137).…”
Section: Role Of Hhex In Pancreas and Diabetesmentioning
confidence: 98%
“…Notably, HHEX was not detected in the pancreatic β-cells and α-cells of adult humans and mice, while it was exhibited in adult pancreatic δ-cells and regulated somatostatin secretion [30]. Lysine-specific demethylase-1 targeted the Hhex locus and promoted the repression of Hhex by facilitating methylation at H3K4me1/2, leading to the prevention of the transition of β-cells to δ-cells [31].…”
Section: Hhexmentioning
confidence: 99%